(untitled) - Mediastream Film (Firm); Universal Pictures (Firm) (Universal Pictures, 2001)
Every night is a championship race on the turbo-charged streets of Los Angeles. Dominic and Johnny are rivals who are the boldest, the baddest, the best, and turn their challengers into dust. Along comes a challenger. Dominic and Johnny know that he is tough and fast, what they dont know is that he is a speed demon detective trying to bust up a theft ring.
Keywords: Drama; Criminal investigation; Los Angeles; California; Automobile racing; Drama; Drama; Video recordings for the hearing impaired; Action and adventure films; Detective and mystery plays; Video recordings; Feature films